2023
DOI: 10.1007/s11356-023-26125-y
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable total factor productivity of transport: considering safety issues and environmental impacts

Abstract: Economy, environment and safety are three important components of sustainable transport. This paper proposes a productivity measurement standard that comprehensively considers economic growth, environmental impact and safety issues, namely sustainable total factor productivity (STFP). We measure the growth rate of STFP in transport sector of OECD countries in terms of Malmquist-Luenberger productivity index by applying data envelopment analysis (DEA). It is found that the growth rate of total factor productivi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Stavropoulos et al [ 47 ] argue that there is a ’U’ shaped relationship between environmental regulations and the competitiveness of China’s IC industry, with positive effects in the long run as long as the regulations are properly designed. Lu and Chen [ 48 ] based on data from the transport sector, found an intermediate value for the effect of environmental regulation intensity on total factor productivity growth. In addition, Tian and Feng [ 49 ] expanding on existing studies, examined the internal structure of different types of environmental regulation on green total factor productivity and showed that there is a significant non-linear relationship between different types of environmental regulation and the intrinsic factors of total factor productivity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Stavropoulos et al [ 47 ] argue that there is a ’U’ shaped relationship between environmental regulations and the competitiveness of China’s IC industry, with positive effects in the long run as long as the regulations are properly designed. Lu and Chen [ 48 ] based on data from the transport sector, found an intermediate value for the effect of environmental regulation intensity on total factor productivity growth. In addition, Tian and Feng [ 49 ] expanding on existing studies, examined the internal structure of different types of environmental regulation on green total factor productivity and showed that there is a significant non-linear relationship between different types of environmental regulation and the intrinsic factors of total factor productivity.…”
Section: Literature Reviewmentioning
confidence: 99%